"Can you call it Okinawan Japanese?": World language delineations of an endangered language on YouTube. (1st September 2016) - Petrucci, Peter R.; Miyahira, Katsuyuki
Abstract : This article addresses a language-versus-dialect discussion that arose out of a series of language lessons on YouTube. Designed to teach Uchinaaguchi, an endangered Ryukyuan language, the video lessons come in two versions, one for Japanese speakers and the other for English speakers. In either version, the video turns to an adroit combination of semiotic modes in an attempt to delineate Uchinaaguchi as a language distinct from Japanese. However, as we demonstrate here, when an endangered language appears on Internet platforms like YouTube, it tends to be framed in one or more world languages, a situation that problematizes the "singularity" of the endangered language (Blommaert, J. 1999. "The Debate Is Closed." In Language Ideological Debates, edited by J. Blommaert, 425–438. Berlin: Mouton de Gruyter). In the case of the Uchinaaguchi lessons, this is especially apparent in viewer commentary written primarily in English and/or Japanese. The analysis of this commentary reveals the ideological effects that world languages can bring into the discussion and delineation of endangered languages online.